Pelatihan Musik Liturgi dan Not Angka Kepada Umat Basis Santa Agnes Theresia Tenau Kupang - Katharina Kojaing; Benediktus Molo; Maria Prisilia Purnamalon; Oktavianus Wale Gare; Geradus Tukan; Dolorosa Apriliany Beatrix (PADMA, 2025)
his training activity aims to make the Santa Agnes base group know and understand Catholic church liturgical music and be adept at singing musical notes so they can sing liturgical songs well. The activity methods carried out are counseling and practice. Activity participants were given an understanding of church liturgical music, the parts of liturgical music, the role and how to perform songs and liturgical music in liturgical celebrations. Training was also carried out on singing number notes to several sample songs. The results of the activity achieved were that the activity participants were able to understand the liturgy in the Catholic church's eucharistic celebration which consists of the liturgy for Ordinary Time, Advent, Lent and Easter. People participating in the activity can also understand the liturgical years A, B and C in the circle of the Catholic church's liturgical period. Activity participants can also be proficient in singing 10 sample songs in number notes with different note values. Activity participants and administrators of the Basis Community Group expressed their happiness because they gained knowledge about liturgy and liturgical music and were able to sing song texts in number notes and recognize the values ​​of number notes in singing.